Transportation Demand Omotenashi at Ijen Corridor: The problems and development strategies - Imma Widyawati Agustin; Septiana Hariyani; Ditha Nurrizkyta (Regional Development Information Center, Universitas Sebelas Maret, 2024)
Ijen was one of the roads in Malang City with land use intensity dominated by education and trade and services, generating land use caused a large movement. The main purpose of the study was to identify some problems and propose solutions to improve the performance of Ijen corridor. The meaning of “Omotenashi” is Japanese-style excellent service mindset consisting of hospitality aspect, familiarity and warmth aspects. The study employed Customer Satisfaction Index (CSI) and Analytical Hierarchy Process (AHP). Analysis of the familiarity aspect was descriptive evaluative interaction of public transport passengers. The analysis of the warmth aspect was descriptive evaluative in physical, social and historical attractiveness. The results showed that hospitality level at Ijen Corridor was 2.038 (hospitable), the familiarity aspect was 61 out of 100 people have interacted on the public transport, while the warmth aspect showed that many buildings are physical attractions and historical areas. The Ijen Corridor's alternative development strategies include raising public awareness of the use of public transportation, restricting access to motorized vehicles, law enforcement, and improving bicycle infrastructure, as well as enhancing the quality of public transportation services, pedestrian facilities, parking management, and carpooling/sharing.